Bringing the Outside In: Examining the Impacts That Climate, Exchange, and Identity Processes Have on Organizationally-beneficial Employee Green Behavior - (:unkn) unknown (My University, 2016)
My dissertation contributes to growing practitioner and researcher interest in the corporate social responsibility topic of employee green behavior, a key strategic input to organizational environmental sustainability efforts. While it has been recognized that employee behavior can significantly impact sustainability efforts (Daily, Bishop, and Govindarajulu, 2009; Ones and Dilchert, 2012), the psychological mechanisms through which this occurs and the precise nature of these behaviors have not been rigorously examined. To address the gaps, my research investigates the interrelationship between organizational and individual factors in motivating organizational citizenship behavior directed toward the natural environment (OCB-E). The model, which derives from social exchange and identity perspectives, considers whether perceptions of organizational climate (psychological climate of care for the natural environment (PCCE)) directly and/or indirectly contribute to OCB-E. Indirectly, I predict that when employees experience a strong PCCE, they experience organizational support (POS), which motivates individuals to undertake OCB-Es. Further, I consider whether identity processes, in the form of employee environmental identity (EEI) and organizational identification (OI), interact with PCCE and/or POS to predict OCB-E. Overall, my proposition is that employees react positively to their organization when its climate reflects a pro-environmental stance. This leads employees via social exchange and/or identity processes to initiate pro-environmental behaviors at work for the benefit of the environment and organization. Bootstrap-adjusted factor analysis using AMOS (v.23) and bias-adjusted hierarchical multiple regression using SPSS (v.22) with the PROCESS plugin (Hayes, 2013) were used to test the hypotheses. Results indicated that a three-dimensional conceptualization of PCCE provided a better fit to the data than a four-dimensional conceptualization. Further, support for a direct relationship between PCCE and OCB-E was found, but not for an indirect relationship through POS. Lastly, the interaction between PCCE and each identity process (EEI and OI) was found to influence OCB-E, and partial support was found for the second-stage moderated mediation of PCCE on OCB-E through the interaction of POS and EEI.
Keywords: Employee Green Behavior; Environmental Citizenship Behavior; Environmental Identity; Environmental Sustainability; Psychological Climte; Social Exchange Theory